Association of screen time with physical activity and BMI in middle school children at Tamil Nadu, India - Kumar, S. Santha; Shirley, S. Alph (International Journal of Contemporary Pediatrics, 2019)
Background: The objective of this study was to find the association of screen time with physical activity and BMI in middle school children in the age group of 11 to 13 years in Tamil Nadu, India. Methods: This cross-sectional observational study was conducted among 139 middle school children aged 11 to 13 years at the state of Tamil Nadu, India from June 2019 to August 2019. Data regarding screen time and physical activity were collected from the children using a predesigned questionnaire and anthropometric measurements done. The data collected were analyzed with suitable statistical methods using SPSS 25 software. Results: Of the 139 children, 46(33.1%) were 11 years, 48(34.5%) were 12 years and 45(32.4%) were 13 years old. 74(53.2%) were male and 65(46.8%) were female. Majority of the study subjects (52.5%) had an average daily screen time of >120 minutes followed by 61 to 120 minutes (28.8%) and ≤60 minutes (18.7%). Of the 139 children studied, only 31.7% (44 children) followed the WHO recommendations of moderate to vigorous physical activity of at least 60 minutes per day, 57.5% of the children had normal BMI, 10.8 % had thinness, 25.2% were overweight and 6.5% were obese. Physical activity was found to decrease with increasing screen time, and this was found to be statistically significant. No statistically significant correlation between screen time and BMI was found. There was statistically significant correlation between physical activity and BMI. Conclusions: There is a significant correlation of screen time with physical activity in this study. Urgent measures need to be taken to decrease screen time and promote a healthy lifestyle.